Association between high serum levels of soluble vascular cell adhesion molecule-1 and obesity in women - Musafer, Karar Nadhum Jawad; Mohammed, Amera Kamal; Al-Thuwaini, Tahreer Mohammed; Huyop, Fahrul; Bradosty, Sarwan Wasman (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Obesity and metabolic disorders are associated with persistent low-level inflammation connected to soluble vascular cell adhesion molecule-1 (sVCAM-1). Recent research highlights its connection to endothelial dysfunction in female obesity. This study aimed to investigate the relationship between sVCAM-1 levels and obesity-related risk factors in women from Kirkuk City, Iraq. METHODS A case-control study was conducted on 90 women aged 20–50, including 43 participants with obesity and 47 healthy controls. Blood samples were collected, processed, and analyzed to measure various biochemical markers, including sVCAM-1. Logistic regression analysis was utilized to examine the association between sVCAM-1 levels and obesity-related parameters. Correlation analysis was performed to assess associations with body mass index (BMI). Statistical analysis was conducted using SPSS software version 23.0. RESULTS Correlation analysis revealed that BMI was significantly correlated with alanine aminotransferase (r = 0.37, p = 0.011), uric acid (r = 0.30, p = 0.04), insulin (r = 0.37, p = 0.01), homeostatic model assessment of insulin resistance (r = 0.47, p = 0.002), and sVCAM-1 (r = 0.53, p = 0.001). These results suggest that elevated sVCAM-1 levels may serve as predictive biomarkers for increased insulin resistance in obese individuals. These findings indicate that sVCAM-1 is strongly linked to female obesity and insulin resistance. CONCLUSIONS This study confirms the potential use of sVCAM-1 as a prognostic biomarker for obesity-related metabolic disturbances and its role in identifying individuals with a higher risk of developing insulin resistance.